The LIM protein RBTN2 and the basic helix-loop-helix protein TAL1 are present in a complex in erythroid cells. - Valge-Archer, V E (1994)
Chromosomal translocations in T-cell acute leukemias can activate genes encoding putative transcription factors such as the LIM proteins RBTN1 and RBTN2 and the DNA-binding basic helix-loop-helix transcription factor TAL1 associated with T-cell acute lymphocytic leukemia. While not expressed in normal T cells, RBTN2 and TAL1 are coexpressed in erythroid cells and are both important for erythroid differentiation. We demonstrate, using anti-RBTN2 and anti-TAL1 antisera, that the LIM protein RBTN2 is not phosphorylated and is complexed with the TAL1 phosphoprotein in the nucleus of erythroid cells. A complex containing both RBTN1 and TAL1 also occurs in a T-cell acute leukemia cell line. Since both RBTN2 and TAL1 are crucial for normal erythropoiesis, these data have important implications for transcription networks therein. Further, since both proteins can be involved in leukemogenesis, these data provide a direct link between proteins activated by chromosomal translocations in T-cell acute leukemia.